Globalny kryzys gospodarczy a zadluzenie Polski - Anna Cudowska-Sojko (Institute of Economic Research (IER), 2014)
– Many countries, including Poland, have been struggling with increasing state debt. The economists noted that the global financial crisis of 2008-2009 significantly impacted the level of foreign debt of these countries. The aim of the study is an analyse of Polish foreign debt in recent years as well as the influence of external factors associated with financial crisis on Polish economy.
Keywords: F62; H63; 330; crisis; state debt